2015
DOI: 10.1108/jpif-02-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Obsolescence – a cause for concern?

Abstract: Purpose – The purpose of this paper is to review what is known about obsolescence and its causes, and provide a critique of how it is reflected in valuations. Design/methodology/approach – The method has been to review the literature on obsolescence to examine the main causes and whether there are approaches that can identify the vulnerability of buildings to the business models they are designed to satisfy becoming outmoded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Scholars 2 Baum (1991) Raftery (1991cited Kirwan and Martin, 1972 Bryson ( 1997 Functional obsolescence Functional obsolescence can be attributed to the condition in which the building no longer fulfils the functions and use requirements for which it was originally designed and loses its utility (Bowei, 1984;Baum, 1991;Guangming, 2011;R. Grover and C. Grover, 2015;Rodi et al, 2015).…”
Section: Number Of Obsolescence Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars 2 Baum (1991) Raftery (1991cited Kirwan and Martin, 1972 Bryson ( 1997 Functional obsolescence Functional obsolescence can be attributed to the condition in which the building no longer fulfils the functions and use requirements for which it was originally designed and loses its utility (Bowei, 1984;Baum, 1991;Guangming, 2011;R. Grover and C. Grover, 2015;Rodi et al, 2015).…”
Section: Number Of Obsolescence Typesmentioning
confidence: 99%
“…Locational obsolescence is where an area suffers from devaluation. It reflects the fact that part of the value of any property is determined by the neighbourhood in which it is located (R. Grover and C. Grover, 2015). Locational obsolescence occurs when buildings located within a particular area suffer from devaluation because the area is seen as less attractive by current or prospective occupiers (Pinder and Wilkinson, 2001).…”
Section: Identifying Building Obsolescencementioning
confidence: 99%
See 1 more Smart Citation
“…2, 2018 regulatory changes (affecting minimum requirements). For an in-depth taxonomy and an extensive review of the nature of underlying causes, see GROVER, GROVER (2015). In the introductory section of their article, the same authors provide a concise but fitting explanation of what obsolescence due to changing consumer behavior means.…”
Section: Deterioration and Obsolescencementioning
confidence: 99%
“…A closer look at the cause of the problem revealed that obsolescence should be addressed at the design stage and not at the Zone of Obsolescence as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%